A Modeling Approach for Lahar Hazard Assessment: the Case of Tamasagra Sector in the City of Pasto, Colombia (2019)
The computational program Titan2F, a two phase flow modeling program, is used to model several hypothetical scenarios of volcanic origin mud flows (lahars) in order to estimate the spacial and temporary evolution of this potentially destructive natural phenomena at its entrance of the city of Pasto, Colombia through the Mijitayo river basin. The predictions of the program suggest that extremely high and destructive dynamic pressures at the entrance to the city can be expected. In addition, our simulations show that half of the Tamasagra and El Bosque neighbors can be inundated with lahar depths of about 1 meter thickness. The program shows to be capable to deal with the modeling of the effect of the streets and buildings on the flow behavior, showing how the streets channelizes the flow governing the path of it. In addition, our results allow to identify regions where the flow loss most of its energy, where mitigation of risk can be suggested.